Pengaruh Quality of Work Life, Kompensasi, dan Motivasi Kerja Terhadap Organizational Citizenship Behavior (OCB) Pada Karyawan KSP Maju Bersama Jaya Magelang - Amelia, Amanda; Utami, Kristiana Sri (Universitas Maritim AMNI Semarang, 2024)
This study aims to prove and analyze the effect of quality of work life, compensation, and work motivation on organizational citizenship behavior in KSP Maju Bersama Jaya Magelang employees. The research was conducted quantitatively, with the sample analyzed being 14 employees. This research method is carried out in stages starting from the introduction to the processing of data that the author and the preparation of research reports have obtained. The study's results prove that quality of work life, compensation, and work motivation do not partially or simultaneously affect organizational citizenship behavior. Other results show that the magnitude of the influence of quality of work life, compensation, and work motivation on organization citizenship behavior on organization citizenship behavior is 39.0%.